Minimally Invasive Ablation of a Toxic Thyroid Nodule by High-Intensity Focused Ultrasound - Esnault, O. (AJNR Am J Neuroradiol, 2010)
HIFU is used in the treatment of cancer (prostate, breast) and uterine fibroma but not yet in TNs. This case report describes the first successful ablation of a toxic TN with HIFU. TSH and radioiodine scan normalization were achieved without complications and maintained for 18 months. HIFU treatment is a minimally invasive technique that may be an effective safe alternative to radioiodine or surgery in patients with toxic TNs.